IMPLEMENTASI VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Maladisma, Nur; Idawati; Mariati (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
This research is a Classroom Action Research (CAR) with the aim of improving student learning outcomes in Citizenship Education about My School Rules. This study applies learning videos with the research subjects are the students of class III.A in SD Negeri V Sungguminasa, Gowa Regency in the first semester of the 2024/2025 and total of students are 32 students consisting of 15 male students and 17 female students. The instrument used is the Form test of the ability to understand concepts at the end of the cycle. The results of pre-cycle learning with KKTP 70 obtained an average class score of 67.5 with a percentage of learning completeness reaching 71.87%. In cycle I, the average class score increased from 67.5 to 71.6 with a percentage of learning completeness of 78.13%. In cycle II, the average class value increased to 83.12 with a learning completion percentage reaching 93.75%. From the observation data from the pre-cycle to the cycle II stage, there was an increase in student learning completion of 21.88%. Based on these data, it can be concluded that teaching and learning activities using video learning media can improve student learning outcomes. Its because video of learning presented sound and picture so the students can improve their comprehension and meaningful understanding about the concept which will be teaching.